The clinical impact of recent amphetamine exposure in aneurysmal subarachnoid hemorrhage patients - Vitt, Jeffrey R.; Cheng, Roger C.; Chung, Jason; Caton, Travis; Zhou, Bo; Ko, Nerissa; Meisel, Karl; Amorim, Edilberto (Frontiers in Neurology, 2025)
BackgroundAmphetamines possess sympathomimetic properties that can affect cerebral vasculature though conflicting reports exist about their effect on vasospasm risk and clinical outcomes in aneurysmal subarachnoid hemorrhage. This study aimed to characterize the impact of recent amphetamine use on vasospasm development in aneurysmal subarachnoid hemorrhage as well as neurological outcomes.MethodsWe retrospectively screened 441 consecutive patients admitted with a diagnosis of subarachnoid hemorrhage who underwent at least one cerebral digital subtraction angiogram. Patients were excluded if no urinary toxicology screen was performed within 24 h of admission, if there was a diagnosis of non-aneurysmal subarachnoid hemorrhage, or if ictus was greater than 72 h from hospital admission. Vasospasm characteristics were collected from digital subtraction angiography and transcranial Doppler studies.Results129 patients were included and 24 tested positive for amphetamines on urine drug screen. No significant differences were found in respect to patient age, sex, or admission clinical severity scales (Hunt-Hess and modified Fisher) based on amphetamine use. There was no difference in the severity of vasospasm or time to peak severity based on recent amphetamine use. A trend toward more isolated posterior circulation vasospasm was observed in the amphetamine present group (16.7% vs. 4.8%, p = 0.06), while there was higher incidence of anterior circulation vasospasm in the amphetamine absent group (79.2% vs. 94.3%, p = 0.03). There was no difference in delayed cerebral ischemia incidence, length of hospital stay, need for ventriculoperitoneal shunt placement, functional outcome at discharge or hospital mortality based on amphetamine use.InterpretationRecent amphetamine use was not associated with worse vasospasm severity or delayed cerebral ischemia in aneurysmal subarachnoid hemorrhage patients. Further investigations about localized effects in the posterior circulation and impact on long-term functional outcomes are warranted.